2010
DOI: 10.1055/s-0030-1253421
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 (9–36) Amide Metabolite Suppression of Glucose Production in Isolated Mouse Hepatocytes

Abstract: The glucoincretin hormone glucagon-like peptide-1 (GLP-1) augments glucose-stimulated insulin secretion and is in use as an effective treatment for diabetes. However, after its secretion from the intestine, the insulinotropic GLP-1 (7-36) amide hormone is rapidly inactivated by enzymatic cleavage by the diaminopeptidyl peptidase-4 giving rise to GLP-1 (9-36) amide. Inasmuch as most of the circulating GLP-1 is in the form of the metabolite GLP-1 (9-36) amide it has been suggested that it has insulin-like action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 30 publications
3
66
1
Order By: Relevance
“…GLP-1R is not expressed in fat tissue, but treatment with GLP-1 elicited insulinomimentic effects in 3T3-L1 cells, and exendin-(9-39) enhanced the effect [27]. GLP-1(9-36) amide, a GLP-1 cleaved product, directly suppressed glucose production in isolated mouse hepatocytes ex vivo independent of the GLP-1R, an effect augmented by exendin-(9-39) [43]. Finally, we have recently shown that treatment of human primary liver cultures (negative to GLP-1R) with exendin-4 increased cell proliferation and enhanced PDX-1-induced liver to pancreas trans-differentiation process [44].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1R is not expressed in fat tissue, but treatment with GLP-1 elicited insulinomimentic effects in 3T3-L1 cells, and exendin-(9-39) enhanced the effect [27]. GLP-1(9-36) amide, a GLP-1 cleaved product, directly suppressed glucose production in isolated mouse hepatocytes ex vivo independent of the GLP-1R, an effect augmented by exendin-(9-39) [43]. Finally, we have recently shown that treatment of human primary liver cultures (negative to GLP-1R) with exendin-4 increased cell proliferation and enhanced PDX-1-induced liver to pancreas trans-differentiation process [44].…”
Section: Discussionmentioning
confidence: 99%
“…Since in situ perfused livers reflected the in vivo conditions of the animal immediately before the liver isolation (Galende et al 2009;OliveiraYamashita et al, 2009) and considering that mice treated with a HFD were a suitable experimental model to induce the liver glucose overproduction (Tomas et al 2010;Wu et al 2010), this experimental approach was used. As showed by Table 1, the treatment with infliximab prevented the glucose overproduction during the infusion of L-alanine in the liver from HFD mice (p<0.05: HFD + Infliximab vs. HFD + Saline).…”
Section: Resultsmentioning
confidence: 99%
“…However, metformin shows several adverse effects, including nausea, vomiting, diarrhea, flatulence (Florez et al 2010) and is contraindicated in conditions that could increase the risk of lactic acidosis, including kidney disorders, lung disease and liver disease (Friesecke et al 2010). Considering that except metformin there are only a few pharmacological alternatives to reduce the liver glucose overproduction (ADA 2010;Tomas et al 2010), the development of new drugs, which influences this metabolic process must be investigated. In this context, the anti-TNF-alpha monoclonal antibody infliximab showed beneficial effects not only for the diseases such as rheumatoid arthritis, Crohn's disease, and psoriatic arthritis (Karampetsou et al 2010) but also for type 2 diabetic patients (Ursini 2009;Ursini et al 2010;Yazdani-Biuki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that EGLP-1 reduced blood glucose by improving the function of β-cells. It has been reported that GLP-1 possesses a number of anti-diabetic actions, including glucose-dependent insulin secretion (insulinotropic action) dependent on GLP-1R [9] and an insulin-like (insulinomimetic) action independent on GLP-1R [38][39][40][41] in addition to its insulinotropic action. This suggests that EGLP-1 may have a new role in improving β-cell function independently of GLP-1R.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%